Assessment of the Surface Topography of Al 99.5% Tubular Products Formed by Cold Flow Forming Technology. (2015) - Ekinovic, S.; Đukic, H.; Plancic, I.; Begovic, E.
Abstract: The process of cold flow forming (CFF) is a method of plastic deformation in which by using tools in the form of balls, rollers or flowforming wheel on special mandrel hollow cylindrical or conical parts, such as the various geometric combinations are obtained. The technology is classified as a NSF technology ("net-shape forming") because it allows production of parts that are without any or with minimal subsequent modification of functional area and as such can be considered as a final product for installation. This paper shows an example of producing 99.5% Al tube workpieces by means of CFF technology. The analysis of the quality of the resulting outer surfaces by measuring the geometrical characteristics of profiles with special reference to the waviness outer surface of workpieces has been performed. The measurement was performed on 3D optical microscope.